Mediterranean Diet and Cardiovascular Risk: Are We There Yet? - Huxley, Rachel; Clifton, P. (2013)
A Mediterranean-style diet has long been propounded to confer substantial health-promoting effects, particularly those relating to cardiovascular disease. The diet itself represents a concept that varies across the Mediterranean region but is characterized by relatively high intakes of olive oil, legumes, fruits and vegetables, unrefined cereals, fish, and red wine-all of which are purported to be beneficial at reducing cardiometabolic risk. Most of the evidence to date on the effects of the Mediterranean diet has come from large prospective cohort studies, clinical feeding studies, and small randomized trials of the effects of different components of the diet on cardiovascular and metabolic risk factors. In recent years there have been several meta-analyses published that have attempted to aggregate the large amounts of data on the topic and the first randomized trial of the effects of the Mediterranean diet on cardiovascular outcomes in a primary care setting. The findings from these studies will be discussed as so will the most recent evidence as to the biological mechanisms that may underpin the association between the Mediterranean diet and cardiovascular risk. © 2013 Springer Science+Business Media New York.